Challenges Facing Decentralization and Community Participation in Local Development in Capricorn District Municipality, South Africa. (1st May 2016) - Asha, Aklilu A.; Belete, Abenet; Moyo, Theresa
Abstract: This study aims to investigate the key challenges facing decentralization and community participation in local development processes in Capricorn District Municipality (CDM). A qualitative case study design was adopted to examine critical factors influencing decentralization and community participation in the two local municipalities under CDM. Primary data was collected through interviews with officials and community representatives using non-probability purposive sampling, and cross-examined along with secondary sources. It was found, inter alia, that poor decision-making, weak institutional capacity, lack of commitment, poor responsiveness, and lack of inclusiveness were the major critical issues facing the local municipalities. In conclusion, if the local government embark on drastic measures to address such deterring factors, the decentralization process, which has taken place through the formation and functioning of the CDM will lead to a comprehensive citizen participation in the design and delivery of services and development.